2014
DOI: 10.4103/1947-2714.145466
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of interleukin-10 gene promoter are associated with schizophrenia in Saudi patients: A case-control study

Abstract: Background:Interleukin-10 (IL-10) gene is considered as a potential candidate gene in schizophrenia association studies. The polymorphisms on IL-10 gene have been reported to be linked with susceptibility to the development of schizophrenia within consistent results.Aims:The aim of this case-control study was to examine whether the -1082A/G, -819T/C, and -592A/C polymorphisms in IL-10 gene are implicated in schizophrenia development in the Saudi population.Materials and Methods:Molecular genotyping of IL-10 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
(86 reference statements)
1
10
1
Order By: Relevance
“…These findings may also point out potential biases in previous studies regarding the causes of elevated CRP levels in SZ patients, such as pleiotropic effects within chosen instruments and/or reverse causality ( 13 ). In addition to CRP variants, other recent studies have identified other variants associated with SZ including variants in the major histocompatibility complex region on Chromosome 6p21 ( 54 ), harboring many cytokine genes ( 55 57 ), and in the TNF promoter ( 58 ), IL10 promoter ( 59 ), IL1B ( 60 ) and C4 ( 61 ). To make a long story short, CRP has been robustly associated with the SZ risk, however it remains unclear if this association may be due to confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may also point out potential biases in previous studies regarding the causes of elevated CRP levels in SZ patients, such as pleiotropic effects within chosen instruments and/or reverse causality ( 13 ). In addition to CRP variants, other recent studies have identified other variants associated with SZ including variants in the major histocompatibility complex region on Chromosome 6p21 ( 54 ), harboring many cytokine genes ( 55 57 ), and in the TNF promoter ( 58 ), IL10 promoter ( 59 ), IL1B ( 60 ) and C4 ( 61 ). To make a long story short, CRP has been robustly associated with the SZ risk, however it remains unclear if this association may be due to confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for how elevated CRP levels are linked to schizophrenia requires a well-defined experimental analysis. In addition to CRP variants, other recent studies have identified several inflammatory genetic variants associated with schizophrenia and bipolar disorder, which include variants in the major histocompatibility complex (MHC) region on Chromosome 6p21 [ 72 ]—harboring many cytokine genes [ 54 , 73 76 ]—and in the IL10 promoter [ 77 ], TNF promoter [ 78 ], IL1B [ 79 ], and C4 [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of allele G was reported to be slightly higher in Iranian Azeri Turkish IBD patients, it did not reach statistical significance [110]. Further, no association of TNF-α(-308G/A) polymorphism with IBD susceptibility was found in Australian [82], Brazilian [60,130], Canadian [100], Chinese [106,131], Czech [132], French [133], Indian [108], Korean [115], Newfoundland [27], Spanish [126], and Turkish [120] populations. The reason for these differences in the TNF-α genetic associations with IBD etiology might be the variations in sample size, genotyping methods, and/or ethnicity itself as frequencies of alleles and genotypes of TNF-α (-308G/A) also vary in different ethnic healthy populations worldwide [39] ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The -1082G, -819C, and -592C (GCC) alleles have been associated with elevated levels of IL-10 production [78], while ACC and ATA haplotypes show intermediate and low IL-10 gene transcription, respectively [79]. These IL-10 gene polymorphisms are reported to be associated with susceptibility/development to various inflammatory disorders [40,[80][81][82]. However, data are limited and inconsistent and therefore do not allow drawing unequivocal conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation